PENGARUH PROFITABILITAS DAN GREEN ACCOUNTING TERHADAP NILAI PERUSAHAAN - Sergius Fribontius Bon (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the effect of profitability and green accounting on firm value. The population of this study includes all mining companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The sample was determined using a purposive sampling technique, with 12 companies. The analytical method used was panel data regression. The results show that profitability has a positive effect on firm value, while green accounting does not show a significant effect.